English teacher education: the need for a new perspective - Florén Serrano, Celia (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1991)
The paper explores the drawbacks that may arise from an excessive emphasis on either teacher education or teacher training in the syllabus of the future English language teacher. Then it analyses the present limitations in the teaching practice within the E.U. del Profesorado de E.G.B. and how some of the existing problems might be overecome.